Домовенок Кузька - Александрова Татьяна Ивановна (Серия "Школьная библиотека", 2008)
Экземпляры: ф15 (20220504ԁ) / Инвентарный номер: 63150 / Цена: 45.00 / Сис.шифр: Р2мл / Авт.знак: А 46 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6